Global epidemiology and burden of tetanus from 1990 to 2019: A systematic analysis for the Global Burden of Disease Study 2019 - Jun Li; Zicheng Liu; Chao Yu; Kaiwen Tan; Sijie Gui; Shuang Zhang; Yi Shen (International Journal of Infectious Diseases, 2023)
Objectives: Tetanus is a serious infectious disease. In recent decades, the epidemiology and disease characteristics of tetanus have been reported by many medical workers, but these studies usually have limited sample sizes. Methods: We retrieved all the epidemiological data related to tetanus from the Global Burden of Disease Study 2019, and a secondary analysis was performed to report the global epidemiology and disease burden of tetanus. Results: From 1990 to 2019, the incidence and death rate of tetanus decreased worldwide. In general, high sociodemographic index (SDI) countries have lower age-standard incidence rates and age-standard death rates than low SDI countries. Moreover, in low SDI regions, newborns were the highest-risk group for tetanus. In high SDI areas, half of the tetanus cases occurred in the 70+ years age group. The disease burden of tetanus was significantly higher in males than in females. Conclusion: The disease burden of tetanus decreased significantly worldwide from 1990 to 2019. Neonatal tetanus is serious in low SDI areas, whereas the proportion of elderly tetanus is the highest in high SDI areas. The containment of tetanus in all age groups and sex still requires effort from all sectors.